Machine Learning and Hybrid Modelling for Reaction Engineering: Theory and Applications - Zhang, Dongda; del Río Chanona, Ehecatl Antonio (Royal Society of Chemistry, The, 2023)
Machine Learning and Hybrid Modelling for Reaction Engineering summarises latest research and fills a gap in methodology development of hybrid models for reaction engineering applications.